2015
DOI: 10.1007/s10461-015-1051-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consistent Condom Use Among Homeless Men Who Have Sex with Women and Engage in Multiple Sexual Partnerships: A Path Analysis

Abstract: Consistent condom use is the main strategy aimed at preventing individuals from acquiring HIV through sexual intercourse. The mechanism of consistent condom use among a high-risk homeless subpopulation-homeless men who have sex with women and also engage in multiple sexual partnerships-remains unclear. This study identified 182 homeless men who engaged in multiple sexual partnerships from a representative sample of homeless men, who self-identified as heterosexual, using meal line services in Downtown Los Ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
2
12
1
Order By: Relevance
“…Among a cross-sectional sample of sexually active homeless adults from an understudied region in the southwestern United States, we examined the prevalence of recent sexual risk behaviors, including having condomless sex, new sexual partners, and having multiple sexual partners in the past year. We found lower rates of condomless sex than have been found in other studies of homeless adults [ 7 , 10 ]. We also found that the proportion of individuals who had condomless sex, new sexual partners, and multiple sexual partners in the past 12 months was higher among those younger than 25 years old than among those 25 years and older.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Among a cross-sectional sample of sexually active homeless adults from an understudied region in the southwestern United States, we examined the prevalence of recent sexual risk behaviors, including having condomless sex, new sexual partners, and having multiple sexual partners in the past year. We found lower rates of condomless sex than have been found in other studies of homeless adults [ 7 , 10 ]. We also found that the proportion of individuals who had condomless sex, new sexual partners, and multiple sexual partners in the past 12 months was higher among those younger than 25 years old than among those 25 years and older.…”
Section: Discussioncontrasting
confidence: 74%
“…For example, condomless sex is a prevalent HIV risk behavior among individuals experiencing homelessness. In studies of homeless men, over two-thirds of participants reported having condomless sex in the past six months [ 10 ] and each additional sex partner has been found to be associated with an increase of more than two times the odds of engaging in condomless sex [ 11 ]. In a sample of both male and female sexually active homeless adults, approximately 76% reported having condomless sex [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ii) Frequency of condom use is a factor because consistent condom use is the main strategy aimed at preventing individuals from acquiring HIV through sexual intercourse [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Factors predisposing individuals to use condoms include social-demographic characteristics {e.g., age [13], gender [7, 9, 14], sexual orientation [14, 15], race [13–15], marital status [13], education level [13, 15], education backgrounds of parents [9]}, and attitudinal-belief variables such as HIV-related knowledge [8, 13] and attitudes towards condom use [7, 8, 10, 11, 14, 17]. Factors inhibiting and promoting use of condoms (i.e., enabling factors) can be measured with multiple indicators such as their own personal resources {e.g., income [15] and self-efficacy of condom use [7, 8, 11, 14, 16, 17]} and the availability of health services in their community of residence such as condom available when having sex [10] and exposure to a community-level HIV prevention intervention [13, 16].…”
Section: Conceptual Frameworkmentioning
confidence: 99%